1992
DOI: 10.1037/0278-7393.18.2.368
|View full text |Cite
|
Sign up to set email alerts
|

Direct coding for frequency of occurrence.

Abstract: Using an interference paradigm, we demonstrate that there is a place for a direct coding mechanism in a comprehensive theory of frequency coding. Ss were presented words whose frequency was judged later. Under one set of instructions, these words were coded in terms of numerical associates; under another set of instructions, the coding was governed by nonnumerical associates. The condition using numerical associates resulted in frequency estimations that were of lesser quality than those produced in the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 33 publications
(53 reference statements)
4
31
1
Order By: Relevance
“…Frequencies are fairly accurately and almost automatically monitored in humans and animals (e.g., Cosmides & Tooby, 1996;Jonides & Jones, 1992). From this research it follows that physicians and lay people alike can understand risks better when the information is communicated in natural frequencies rather than in probabilities or percentages.…”
Section: Ppv = P(hiv)p(pos | Hiv) P(hiv)p(posmentioning
confidence: 87%
“…Frequencies are fairly accurately and almost automatically monitored in humans and animals (e.g., Cosmides & Tooby, 1996;Jonides & Jones, 1992). From this research it follows that physicians and lay people alike can understand risks better when the information is communicated in natural frequencies rather than in probabilities or percentages.…”
Section: Ppv = P(hiv)p(pos | Hiv) P(hiv)p(posmentioning
confidence: 87%
“…There was no evidence that JOFs were influenced by the spatial numerosities. In a related study, Jonides and Jones (1992) found that JOFs to quantitativewords (e.g. twins, quadrangle, couple, triplets) were less accurate than JOFs to control words, a result they attributed to direct coding of frequency of occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of its processes, however, information encoding appears to result in highly accurate frequency estimates. As Jonides and Jones (1992) put it, "Ask about the relative numbers of many kinds of events, and you are likely to get answers that reflect the actual relative frequencies of the events with great fidelity" (p. 368; see also Zacks & Hasher, 2002, p. 27). Using their conclusion as a starting point, we now present two mechanisms of how people could make risk judgments on the basis of directly encoded frequency information.…”
Section: Direct Encodingmentioning
confidence: 99%